KEPUTUSAN PENDANAAN, UKURAN PERUSAHAAN, LABA PERUSAHAAN DAN RISK BASED CAPITAL, SEBAGAI VARIABEL PREDIKTOR NILAI PERUSAHAAN ASURANSI DI INDONESIA - Adnan Hakim; Al Asy Ari Adnan Hakim (Mega Aktiva, 2018)
This research is to analyze and determine the contribution of factor funding decisions, the size of the company, the company's profit and risk based capital simultaneously and partially to the company's value. The approach used is The correlation between variables, while the sampling technique is purposive sampling were selected based on certain criteria as much as 10 insurance companies listed on the Jakarta Stock Exchange in parentheses period of 7 years. The data used is secondary data that is accessed from the JSE's website, and the methods of analysis used is multiple linear regression. The results of this study found that the funding decision does not significantly increase the value of the company, while the size of the company and the company's profit as well as partial risk-based capital has a positive and significant effect in increasing the value of the company. Then simultaneously discovered all the observed variables have contributed simultaneously to enhance shareholder value. This means that, to increase the value of the company, it needed the funding decision is effective and efficient, the size of the company and the company's profit and risk-based capital.